Influence of particle properties on powder bulk behaviour and processability - Shah,UV; Karde,V; Ghoroi,C; Heng,JYY (International Journal of Pharmaceutics, 2017)
Understanding interparticle interactions in powder systems is crucial to pharmaceutical powder processing. Nevertheless, there remains a great challenge in identifying the key factors affecting interparticle interactions. Factors affecting interparticle interactions can be classified in three different broad categories: powder properties, environmental conditions, and powder processing methods and parameters. Although, each of these three categories listed is known to affect interparticle interactions, the challenge remains in developing a mechanistic understanding on how combination of these three categories affect interparticle interactions. This review focuses on the recent advances on understanding the effect of powder properties, particularly particle properties, its effect on interparticle interactions and ultimately on powder bulk behaviour. Furthermore, this review also highlights how particle properties are affected by the particle processing route and parameters. Recent advances in developing a particle processing route to prepare particles with desired properties allowing desired interparticle interaction to deliver favoured powder bulk behaviour are also discussed. Perspectives for the development of potential particle processing approaches to control interparticle interaction are presented.